Regulatory B Cells (Bregs) Inhibit Osteoclastogenesis and Play a Potential Role in Ameliorating Ovariectomy-Induced Bone Loss - Sapra, Leena; Bhardwaj, Asha; Mishra, Pradyumna Kumar; Garg, Bhavuk; Verma, Bhupendra; Mishra, Gyan C.; Srivastava, Rupesh K. (Frontiers in Immunology, 2021)
Increasing evidences in recent years have suggested that regulatory B cells (Bregs) are one of the crucial modulators in various inflammatory disease conditions. However, no study till date have investigated the significance of Bregs in modulating osteoclastogenesis. To the best of our knowledge, in the present study, we for the first time examined the anti-osteoclastogenic potential of Bregs under in vitro conditions and observed that Bregs suppress RANKL induced osteoclastogenesis in a dose dependent manner. We further elucidated the mechanism behind the observed suppression of osteoclasts differentiation via Bregs. Our results clearly suggested that the observed anti-osteoclastogenic property of Bregs is mediated via production of IL-10 cytokine. Next, we explored whether Bregs have any role in mediating inflammatory bone loss under post-menopausal osteoporotic conditions in ovx mice. Remarkably, our in vivo data clearly suggest that the frequencies of both CD19+IL-10+ Bregs and CD19+CD1dhiCD5+IL-10+ “B10” Bregs were significantly reduced in case of osteoporotic mice model. Moreover, we also found a significant reduction in serum IL-10 cytokine levels in osteoporotic mice, thereby further supporting our observations. Taken together, the present study for the first time establishes the direct role of regulatory B cells in modulating osteoclastogenesis in vitro. Further, our in vivo data suggest that modulations in percentage of Bregs population along with its reduced potential to produce IL-10 might further exacerbate the observed bone loss in ovx mice.